Pressure and temperature-dependent Raman spectra of MoS2 film - Li, Xue; Li, Jinhua; Wang, Kai; Wang, Xiaohua; Wang, Shuangpeng; Chu, Xueying; Xu, Mingze; Fang, Xuan; Wei, Zhipeng; Zhai, Yingjiao; Zou, Bo (Applied physics letters, 2016)
Molybdenum disulfide (MoS2), a relatively new and exciting two-dimensional graphene-like material, has been attracting more and more attentions from the researchers due to its unique structural and fascinating properties. The potential application of MoS2 under high-pressure and low-temperature is expected, while the related research is few at present. In this paper, quadrilayer MoS2 was synthesized by chemical vapor deposition, and its structural properties under different pressures (0–20.7 GPa) and temperatures (10–300 K) were investigated via the Raman spectra. We find that the lattice of quadrilayer MoS2 is not damaged and the quadrilayer MoS2 exhibits good semiconductive properties under large variable pressures from atmospheric to 20.7 GPa, which is much different to its bulk and single crystalline phases. In addition, the lattice structures of the quadrilayer MoS2 are stable in 10–300 K, and the Grüneisen parameters of E1 2g and A1g modes are smaller than that of bulk. This study indicates that quadrilayer MoS2 has a better prospect in high-pressure and low-temperature environment.